What Extraterritorial Application of Competition Law Means for MNCs - Michael Ristaniemi (My University, 2022)
Several competition law regimes around the world, including the EU and the USA, have adopted rules allowing their respective authorities to apply domestic competition law to activities occurring outside of their territory’s borders. This paradigm presents a clear challenge especially to multinational corporations ("MNCs") that operate on an international scale and which consequently must concurrently adhere to the rules and regulations of several – and potentially conflicting – jurisdictions in their business operations. Moreover, competition law can be and frequently is used as a tool for furthering a single region’s goals in international trade and politics. One visible avenue of doing so is by applying competition laws on an extraterritorial basis. Last, the coherence of jurisprudence itself is damaged by allowing competing legal doctrines to apply simultaneously within a single jurisdiction as they would, should a foreign nation’s competition laws be applied extraterritorially. All of this effectively constitutes a barrier to trade, which hits MNCs hardest in the form of legal uncertainty, increased costs and added administrative burden.
The author studies the legitimacy and breadth of extraterritorial application of competition law and discusses its main implications for MNCs as well as suggests a potential way forward in the form of increased regional cooperation between competition authorities and legislators.